Physicochemical Characteristics and HPLC Determination of Alpha-Tocopherol in Eighteen Edible Vegetable Oils Marketed in Nigeria - Adejumo, Olufunmilayo Ebunoluwa; Popoola, Elizabeth Ayodele; Bamiro, Oluyemisi Adebowale; Daodu, John Olabanji; Olaitan, Olatunde James (Dhaka University Journal of Pharmaceutical Sciences, 2021)
Eighteen brands of vegetable oils available in the local market were extracted with n-hexane before analysis for alpha-tocopherol by RP-HPLC method. The chromatographic separation occurred isocratically with methanol-water [96:4%v/v] at 0.9 ml/min flow rate. Tocopheryl acetate was the internal standard and alpha-tocopherol was eluted at 7.87 min. Free fatty acids value [FFAVs], peroxide value [PV], iodine value [IV] and saponification values [SV] were determined as quality parameters. Calibration curve was linear [r2 0.9969] and the method was precise with relative standard deviation of 0.35% and mean recovery, 87.39%. Alpha-tocopherol concentration ranged from 0-9.22 mg/100g with the highest in Tropical sunflower oil [9.22 mg/100g] and the lowest [1.16 mg/100g] in Laziz oil. Alpha-tocopherol was not detected in unbranded, local palm oil. The calculated percentage daily value [% DV] of vitamin E ranged from 0- 8.60%. Significant difference [p<0.05] between % DV and recommended dietary allowance [RDA] of vitamin E was observed. FFAs and PV ranged from 0.11-0.74% and 0.99-11.55 meq/kg while IV and SV ranged from 26.71-37.03 g/100g and 4.14-43.68 mg KOH/g, respectively. Seventeen samples [94%] were found to be within the acceptable limits while one [6%], failed for both quality parameters and α-tocopherol test. Strict regulatory control is advocated for these oils to safeguard the public health. Dhaka Univ. J. Pharm. Sci. 20(1): 49-57, 2021 (June)